Errors resulting from assuming opaque Lambertian clouds in TOMS ozone retrieval - Liu, X.; Newchurch, M.J.; Loughman, R.; Bhartia, P.K. (Journal of quantitative spectroscopy & radiative transfer, 2004)
Accurate remote sensing retrieval of atmospheric constituents over cloudy areas is very challenging because of insufficient knowledge of cloud parameters. Cloud treatments are highly idealized in most retrieval algorithms. Using a radiative transfer model treating clouds as scattering media, we investigate the effects of assuming opaque Lambertian clouds and employing a Partial Cloud Model (PCM) on Total Ozone Mapping Spectrometer (TOMS) ozone retrievals, especially for tropical high-reflectivity clouds. Assuming angularly independent cloud reflection is good because the Ozone Retrieval Errors (OREs) are within 1.5% of the total ozone (i.e., within TOMS retrieval precision) when Cloud Optical Depth (COD)⩾20. Because of Intra-Cloud Ozone Absorption ENhancement (ICOAEN), assuming opaque clouds can introduce large OREs even for optically thick clouds. For a water cloud of COD 40 spanning 2– 12 km with 20.8 Dobson Unit (DU) ozone homogeneously distributed in the cloud, the ORE is 17.8 DU in the nadir view. The ICOAEN effect depends greatly on solar zenith angle, view zenith angle, and intra-cloud ozone amount and distribution. The TOMS PCM is good because negative errors from the cloud fraction being underestimated partly cancel other positive errors. At COD⩽5, the TOMS algorithm retrieves approximately the correct total ozone because of compensating errors. With increasing COD up to 20–40, the overall positive ORE increases and is finally dominated by the ICOAEN effect. The ICOAEN effect is typically 5–13 DU on average over the Atlantic and Africa and 1–7 DU over the Pacific for tropical high-altitude (cloud top pressure ⩽300 hPa ) and high-reflectivity (reflectivity ⩾ 80%) clouds. Knowledge of TOMS ozone retrieval errors has important implications for remote sensing of ozone/trace gases from other satellite instruments.